Radial Tree in Bunches: Optimizing the use of space in the visualization of radial trees - Armando Arce-Orozco; Luis Camacho-Valerio; Steven Madrigal-Quesada (INCISCOS'17: Proceedings of the International Conference on Information Systems and Computer Science, 2017)
The graphical representation of information hierarchies makes it easy to recognize the relationships between the different elements of such structures. The radial tree is a technique for drawing hierarchies that is visually attractive, intuitive and uses space in an efficient way. Although the technique was developed in the late 1970s, it has recently acquired more interest due to its use in several modern information visualization systems. In this paper, we present a brief review of the basic algorithms to drawing radial trees and propose a new algorithm that allow to make a more efficient use of the available space.